2022
DOI: 10.3390/ijerph19116473
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of One-Time Relaxation Training on Attention Efficiency Measured by Continuous Performance Test in Depressive Disorders

Abstract: Introduction: People with depression often complain of dysfunction in cognitive processes, particularly attention. Pharmacotherapy is one of the most commonly used methods of treating depressive disorders and related attention difficulties. Patients also benefit from various forms of psychotherapy and frequently support themselves with alternative therapeutic methods. The purpose of this study was to examine whether a 15-min-long relaxation training session could improve the efficiency of attention and percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…A recent study examined the attention efficiency as determined by the perceptual speed index measured using the attention and perceptiveness test in people with depression [24]. The results showed that a 15-minute-long, one-time AT session improved the efficiency of attention and perceptiveness in individuals diagnosed with depressive disorders [24].…”
Section: Effects Of Autogenic Training On Mood Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study examined the attention efficiency as determined by the perceptual speed index measured using the attention and perceptiveness test in people with depression [24]. The results showed that a 15-minute-long, one-time AT session improved the efficiency of attention and perceptiveness in individuals diagnosed with depressive disorders [24].…”
Section: Effects Of Autogenic Training On Mood Disordersmentioning
confidence: 99%
“…A recent study examined the attention efficiency as determined by the perceptual speed index measured using the attention and perceptiveness test in people with depression [24]. The results showed that a 15-minute-long, one-time AT session improved the efficiency of attention and perceptiveness in individuals diagnosed with depressive disorders [24]. The pilot study by Ramirez-Garcia and colleagues [25] has demonstrated that participants affected by human immunodeficiency virus (HIV) reported better emotion management and improvements in depressive symptoms and quality of life following the AT intervention.…”
Section: Effects Of Autogenic Training On Mood Disordersmentioning
confidence: 99%